Development of immobilized keratinase and investigation of its efficiency on edible bird nest cleaning process - Sharifah Zafierah, Syed Badrulzaman (2022)
The edible Bird Nest (EBN) cleaning process is one of the important processes in the production of EBN and the most tedious part in the production of EBN because it requires a long time. Feathers are the most impurities found in EBN that are made up of stable structures because of the large abundance of the rigid protein keratin. For this reason, immobilized keratinase is utilized in the cleaning process of EBN. Therefore, this study aims to investigate factors affecting keratinase-CLEA preparation using different parameters, to analyze the hydrolysis efficiency of the Keratinase-CLEA in optimization of reaction conditions and to study the effect of Keratinase-CLEA on EBN quality in cleaning treatment process and the compositions. In the present study, keratinase immobilization was performed using different parameters such as type of precipitants, precipitant concentration, glutaraldehyde concentration, cross-linking time, type of additive and additive concentration. Then, keratinase-CLEA was characterized using different parameters such as temperature optimum, thermal stability, pH optimum, pH stability, reusability, Field Emission Scanning Electron Microscopy (FESEM) and Fourier Transform Infrared (FTIR) Spectroscopy. In order to analyze the performance of keratin hydrolysis using keratinase-CLEA, the screening process was done using OFAT and FFD, followed by optimization of temperature and enzyme and substrate concentration using CCD. In addition, the kinetic parameters of Km, Vmax, Kcat and Kcat/Km were also conducted in this study. Finally, keratinase-CLEA was applied to the cleaning process of EBN and the resulted EBN was analyzed based on their cleaning quality, reusability and proximate analysis. From the finding, the best parameters for the keratinase immobilization were found at 100% ammonium sulfate, 100 mM glutaralaldehyde and 14 hours cross-linking time to form keratinase-CLEA with the best enzyme relative activity (127.34 %). The reusability analysis found that keratinase-CLEA retained more than 40 % keratinase activity after 5 cycles of cleaning process. Therefore, the performance of keratin hydrolysis using keratinase-CLEA was further investigated using OFAT, FFD and CCD and the most significant parameters are temperature (50 °C), enzyme concentration (180 mg/ml) and substrate concentration (0.25 %). The kinetic analysis reported that keratinase-CLEA have high catalytic efficiency compared against the free enzyme by using parameters such as Km (0.088 mM-1), Vmax (9.766 mmol L-1 min-1), Kcat (0.037 s-1) and Kcat/Km (0.416 mM s-1). Then, for the time analysis comparison, it was found that keratinase-CLEA required 30 minutes to produce cleaned EBN while water required 40 minutes and the keratinase-CLEA can be used up to 5 cycles for the cleaning process of EBN compared to water only. Finally, the proximate analysis reported that the composition of crude protein (57.6 % w/w) and carbohydrate (22.3 % w/w) of EBN cleaned using keratinase-CLEA have higher content than EBN cleaned using water. Hence, keratinase-CLEA was proven to be used to hydrolyze keratin from feathers and this solution can be used to improve the cleaning process of EBN by reducing time consumption.